QUALITY OF GENOMIC DNA EXTRACTED FROM MAIZE (Zea mays L.) VARIETIES GROWN IN ABIA STATE, NIGERIA USING BY CETYLTRIMETHYLAMMONIUM METHOD - Ndukwe, Okorie; Edeoga, Hilary; Omosun, Garuba; Ume, Maria (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
A study was carried out at the laboratory of Plant Science and Biotechnology Department Michael Okpara University of Agriculture, Umudike, Abia State Nigeria to assess the quality of the genomic DNA extracted from 10 maize varieties grown in Abia State, Nigeria and to determine the suitability of extracted DNA for polymerase chain reaction. The grains of 10 maize (Zea mays L.) varieties namely Oba-98, SAMMAZ-28, SUWAN-1-SR-Y, BR9928-DMRSR-Y, ART/98/SW-1-1, MDV-3, BR9943-DMR-SR-W, TZPB-SR-W, Oba super-2, SDM-2 provided by National Seed Company of Nigeria were used for the study. The result revealed that with the exception of Oba- 98, MDV-3 and TZPBSR-W, all the other varieties recorded values above 1.7 for A260/A230 indicating that the DNA may not have been contaminated with polysaccharide. This indicates that maize seed yielded high quality DNA for PCR amplification.